PENGARUH CITRA MERK, HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN PADA PRODUK ZARA DI PONDOK INDAH MALL 2 JAKARTA SELATAN - Listyowat, Dwi; Rahmat, Ade; Dewi, Sita; Hermawan, Francisca (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Consumers in buying goods and services consider the quality of the product and also the price. Another consideration is the brand image of the goods or services to be purchased. If the brand of goods is well known enough, consumers will buy these goods. Affordable prices, good product quality and a recognized product brand image encourage consumers to repurchase these products so that consumers become loyal. Clothing is one basic product that human need. Many types of clothing are created according to the wishes of consumers, so that business opportunities in fashion arise. Fashion includes clothing and accessories. Business competition in the fashion sector is getting tighter. Zara as one of the foreign retailers enlivened the fashion in Indonesia. Zara stores can be found in several places, one of them is in Pondok Indah Mall2. Zara has always been a trend setter and created a very good brand image, the best price, and the quality of its products has advantages. By providing quality products, it will provide satisfaction to consumers so as to create loyalty in consumers. This study aims to determine the effect of brand image, price, product quality on consumer loyalty to Zara products at Pondok Indah Mall2, either partially or simultaneously. The results showed that partially only product quality has an effect on consumer loyalty to Zara products at Pondok Indah Mall2. Meanwhile, brand image has no effect on consumer loyalty to Zara products at Pondok Indah Mall2. Likewise, price has no effect on consumer loyalty to Zara products at Pondok Indah Mall2. But simultaneously brand image, price, product quality affect consumer loyalty to Zara products at Pondok Indah Mall2.